Smart Biometric Attendance and Monitoring System - Y.S. , Vijaya Lakshmi; V, Jagadeesh Kumar (International Journal of Computer Sciences and Engineering, 2019)
Now in the recent era of attendance system, attendance system is playing a vital role in schools and colleges. Schools and colleges are trying to improve their attendance system day by day. Most of the students are being absent to colleges without intimating their parents. Their parents are unaware of the absenteeism. Keeping these things in mind and in order to overcome the situation [1], RFID based automated attendance system has come into existence. Earlier days RFID technology with BIO metric based was used where he/she can flash the id card and take biometric without attending classes, during the start and end of the College timings. There is a drawback with this system as the attendance is being marked for the entire without attending the classes, which is not an idle situation. In order to have more robust automated attendance systems and to overcome the present situation, we have come up with a new technique of GPS based technology embedded with RFID and Biometric technology. With the advent of a new technique, we can insert GPS based chip in the student`s id card. If any student flashes his or her id card and takes biometric without attending classes and trying to leave the college campus, based on the new technique, we can identify the existence of the particular person. Initially, we have to store our college location (specific location) in a microcontroller. If he/she is not in the college, the microcontroller will send a message to the parents or respective staff. This work is intended to develop a safe and secure student attendance monitoring and also the student’s location by the use of RFID, Bio Metric and GPS based technology. So based on this method message will be sent to respective student’s parent who is absent and not attending the college and similarly to the respective computer Staff.